Penerapan Pendekatan Contextual Teaching And Learning Dalam Meningkatkan Keterampilan Psikomotor Fisika Siswa Di Kelas XI Sma Negeri 1 Ukui - M. Rahmad; Shaiful Ahmad; Azizahwati Azizahwati (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2010)
Research on the psychomotor skill learning physics students through approaches Contextual Teaching andLearning (CTL) grade students performed at the Senior High School 1 (SMA N 1) class XI Ukui the2009/2010 school year. This research aims to describe and analyze the results of studies on aspectspsychomotor skills of students, to basic material energy and work. Collecting data in this study conducted atthe end of the learning process by conducting performance tests to each student. Parameters of this researchis absorptive capacity, learning effectiveness, exhaustiveness individual and classical student learning,exhaustiveness of learning objectives and lesson materials. The results obtained by analysis of the averageabsorption was 87.5% with very good categories, where as the completeness of classical learning of studentswith category 100% complete, and completeness of material is 100% with complete categories. Thus theimplementation of CTL approach is effective and can improve the learning outcomes of studentspsychomotor skills class XI SMA N 1 Ukui.